Diagnostic Accuracy of Risk Malignancy Index (RMI) in Diagnosing Ovarian Carcinoma, Confirming the Diagnosis by Histopathology - Alam, Anam Manzoor; Ali, Syed Salman; Ahsan, Javaria; Ghawas, Syed Ali; Alam, Urooj; Alam, Mustajab (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the diagnostic accuracy of risk malignancy index (RMI) in early diagnosis of ovarian carcinoma, keeping histopathology as gold standard. Study Design: Cross-sectional study. Place and Duration of Study: Department of Obstetrics and Gynecology, Combined Military Hospital, Skardu Pakistan, from Nov 2022 to Nov 2023. Methodology: A total of 106 patients aged 20-60 years with presence of ovarian mass on ultrasonography were included in the study. Risk malignancy index was calculated, and presence or absence of ovarian carcinoma was noted. All patients then underwent surgery, and specimen was sent for histopathology. RMI findings were compared with histopathology report. Results: RMI supported the diagnosis of ovarian carcinoma in 62(58.49%) patients. Histopathology findings confirmed ovarian cancer in 64(60.38%) cases. In RMI positive patients, 57 were True Positive and 05 were False Positive. Among the 44 RMI negative patients, 07 were False Negative whereas 37 were True Negative. Overall sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of risk malignancy index (RMI) in early diagnosis of ovarian carcinoma, confirming the diagnosis by histopathology was 89.06%, 88.10%, 91.94%, 84.08% and 88.68% respectively. Conclusion: This study concluded that diagnostic accuracy of risk malignancy index (RMI) in early diagnosis of ovarian carcinoma is significantly high.